Crystal growth behavior of nanocrystal anatase TiO2: A Rietveld refinement in WPPF analysis - Md. Tarikul Islam; Sahil Aman; Taiful Bayzid; Md. Ashikur Rahaman; Upoma Podder; Gazi. Md. Arifuzzaman Khan; Md. Ashraful Alam (Chemistry of Inorganic Materials)
Novel crystallographic investigation of sol-gel-derived anatase TiO2 nanocrystals synthesized using tetra isopropyl orthotitanate (TIOT) as a precursor at pH 9.0 for hydrolysis promoter. Unlike conventional methods integrated whole powder pattern fitting (WPPF) based Rietveld refinement to quantitatively analyze the crystal structure, phase purity and microstructural features of the synthesized nanoparticles (NPs). The refinement confirmed the formation of 100 ​% pure anatase phase with a tetragonal structural shape [a=b= ​3.7893 ​Å, c= ​9.492 ​Å]. Notably, the study employed seven different crystallite size determination identical models where Scherrer method estimating an average size of 8.87 ​nm. The calculated unit cell volume (136.287 ​Å3), lattice strain (0.76 ​%), microstrain (0.00312), crystallinity (61.399 ​%), crystallinity index (1.44) and dislocation density (0.0127 ​nm−2) indicated lattice expansion and high defect tolerance critical features for catalytic and electronic applications. Peak profiling showed highest preferred orientation along the (101) plane at 2θ= ​25.289°, with a d-spacing of 0.35190 ​nm and an intensity of 6542 cps. SEM confirmed uniformly dispersed, non-agglomerated NPs, while EDS analysis validated elemental purity with 60 ​% Ti and 40 ​% O. This comprehensive structural and surface morphological analysis, combining simple synthesis with advanced refinement, provides a reliable framework for optimizing TiO2 nanocrystals in functional applications.